Qur'anic terminology, translation, and the Islamic conception of religion - Dakake, Maria Massi (Religion, 2019)
A key question in the field of religious studies is the extent to which religion' as a concept translates' in various cultural contexts, with some arguing that it is a purely Western and academic construct. In this article, I argue that the Islamic understanding of religion as a universal category of human experience with various, distinct manifestations is similar to the concept of religion widely operative in the academic discipline of comparative religion; for this reason, Islamic terms related to religion can easily be translated into terminology broadly found in the study of religion, including the term religion' itself. I argue, however, that the apparent ease with which one can translate Islamic religious terminology may obscure some important nuances in the Islamic conception of religion that make it both distinct and internally coherent with its broader view of human nature and of its own particular religious system relative to others. Attentiveness to the semantic range and usage of some key terms in Qur'anic and Islamic terminology regarding religion yields a distinctly Islamic conception of religion that is independent of Western, academic theories of religion.